PERANCANGAN DAN PEMBANGUNAN ATAP HALAMAN MASJID AL ASEL, PERUMAHAN KANOMAN, BANYURADEN, GAMPING, SLEMAN, DIY - Widianti, Anita; Priyo, Mandiyo; Prasetio, Eka; Alpriandi, Mulya (Universitas Ahmad Dahlan, Yogyakarta, 2020)
Al Asel Mosque is one of the mosques in Banyumeneng Hamlet, Banyuraden, Gamping, Sleman, DIY, which was established in 1985. Over time the number of worshipers has increased. The current size of the mosque is no longer sufficient to accommodate people who want to worship, especially Friday prayers and Tarawih prayers in the month of Ramadhan, so that they often spill out to the courtyard of the mosque. Problems arise when it starts to enter the rainy season. The mosque yard covering an area of 12x12 m2 which has been covered by concrete block and marked for prayer can not be used anymore. As a result, prayers had to crowd within the mosque and on the porch, even forced to pray on the terrace of the kindergarten room. This of course reduces the solemnity during worship. The committee of Al Asel Mosque planned to build a roof of the mosque courtyard so that the prayers can pray on the courtyard during rain. The purpose of this activity is to help the committee of Al Asel Mosque realize the roof structure of the mosque's yard covering an area of 12x12m2. The method of activities carried out include designing the roof structure and supervision during the construction process in a few weeks. The design process produced documents consisting of design drawings and budget plans. After the completion of the mosque roof construction, the capacity of pilgrims increased and it is expected that prayers would be more solemn during worship.